2009
DOI: 10.1211/jpp.61.05.0002
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450-mediated metabolism in the human gut wall

Abstract: Objective Although the human small intestine serves primarily as an absorptive organ for nutrients and water, it also has the ability to metabolise drugs. Interest in the small intestine as a drug-metabolising organ has been increasing since the realisation that it is probably the most important extrahepatic site of drug biotransformation. Key findings Among the metabolising enzymes present in the small intestinal mucosa, the cytochromes P450 (CYPs) are of particular importance, being responsible for the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
154
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(165 citation statements)
references
References 217 publications
(409 reference statements)
8
154
0
Order By: Relevance
“…Finally, rat CYP2J3, better known as the arachidonic acid epoxygenase (54), has shown very high 25-hydroxylase activities toward vitamin D 3 and is mostly expressed in the liver (31). CYP2J2, the human counterpart, is mainly involved in the cardiovascular system and intestinal metabolism of antihistamine drugs (55,56). Its 25-hydroxylase activity was much lower and seemed to favor vitamin D 2 over vitamin D 3 (57).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, rat CYP2J3, better known as the arachidonic acid epoxygenase (54), has shown very high 25-hydroxylase activities toward vitamin D 3 and is mostly expressed in the liver (31). CYP2J2, the human counterpart, is mainly involved in the cardiovascular system and intestinal metabolism of antihistamine drugs (55,56). Its 25-hydroxylase activity was much lower and seemed to favor vitamin D 2 over vitamin D 3 (57).…”
Section: Discussionmentioning
confidence: 99%
“…There is now a substantial body of evidence to support the notion that many of the pathophysiological events triggered by ischemia-reperfusion injury are mediated through the production of reactive oxygen species (ROS) and to the subsequent secretion of inflammatory cytokines, such as interleukin-6 (IL-6) and tumor necrosis factor-a (TNF-a) (Carcillo et al, 2003). Previous studies clearly showed that these cytokines and ROS cause a decrease in P450 expression resulting from an enhancement in P450 degradation (Thelen and Dressman, 2009;Vee et al, 2009;Weaver, 2009). These findings led us to hypothesize that the reduction in P450 expression after RBC resuscitation may be caused by the degradation of P450 enzymes rather than the inhibition of P450 synthesis and that CO-RBC may inhibit P450 degradation via the suppression of ROS production or the expression of IL-6 and TNF-a, because it has been demonstrated that CO suppresses the production of both ROS and inflammatory cytokines (Motterlini and Otterbein, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that some caution must be applied when interpreting this data, as the in vitro experiments undertaken herein utilised transformed cell lines, which may not be fully representative of the in vivo tissue. However, we have selected those cell lines previously reported to be amongst the closest models of the relevant primary tissue (Lieber et al, 1976;Thelen and Dressman, 2009;Lin et al, 2012), which may mitigate this potential confounder to some degree.…”
mentioning
confidence: 99%